Fe3O4@Silica Sulfuric Acid: An Efficient and Heterogeneous Nanomagnetic Catalyst in Organic Reactions - Fallah-Mehrjardi, Mehdi (Mini-Reviews in Organic Chemistry, 2017)
Recently Fe3O4@silica sulfuric acid as an efficient nanomagnetically recyclable solid acid catalyst has been synthesized and used in organic transformations. Magnetic nanoparticles were synthesized by simple co-precipitation of FeCl2.4H2O and FeCl3.6H2O in ammonia solution. Then, after addition of tetraethyl orthosilicate in ammonia solution, silica was formed on the surface of magnetite nanoparticles. Finally, the catalyst has been prepared by the functionalization of silica-coated magnetic nanoparticles (Fe3O4@SiO2) using chlorosulfonic acid. The catalyst was characterized by Fourier transform-infrared (FT-IR) spectrometry, X-ray diffraction (XRD) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), vibrating- sample magnetometry (VSM) and thermo gravimetric analyses (TGA). Nano-Fe3O4@silica sulfuric acid was easily recovered from the reaction mixtures by an external magnet and reused several times with no significant decrease in its catalytic activity. In this review, preparation, characterization and applications of this catalyst in organic synthesis has been discussed.
Keywords: organic reactions